1999
DOI: 10.21273/jashs.124.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Inheritance of Phytophthora Root Rot and Foliar Blight Resistance in Pepper

Abstract: The inheritance of resistance to Phytophthora capsici Leonian root rot and foliar blight was compared in two different Capsicum annuum L. var. annuum pod types. The seedling was screened for phytophthora root rot, while a genetically identical stem cutting was screened for phytophthora foliar blight to determine if the same gene(s) confer resistance to both disease syndromes. The susceptible parents were `Keystone Resistan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
64
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 11 publications
7
64
0
Order By: Relevance
“…The progenitor SCM-334 always showed 100 % survival and, in addition, all the members of F 1 were resistant (Table 1). These results agree with those of Walker and Bosland (1999) as regards the dominance of resistance in the F 1 generation.…”
Section: ⎯⎯⎯⎯supporting
confidence: 91%
See 1 more Smart Citation
“…The progenitor SCM-334 always showed 100 % survival and, in addition, all the members of F 1 were resistant (Table 1). These results agree with those of Walker and Bosland (1999) as regards the dominance of resistance in the F 1 generation.…”
Section: ⎯⎯⎯⎯supporting
confidence: 91%
“…The most convincing results suggest that resistance to P. capsici in SCM-334 pepper plants is polygenic and that the three genes that confirm resistance provoke a susceptible-resistant gradient in the segregating generations (Palloix 1986, Gil Ortega et al 1992. However, other researchers have suggested that resistance in SCM-334 might be based on a two gene model (Guerrero and Laborde 1980), while, more recently, Walker and Bosland (1999) observed that the segregation of resistance in F 1 was dominant, but the number of genes required in the F 2 plants is dependent on the susceptible parent.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Tbe pepper line CM334 bas been extensively tested against isolates worldwide and bas demonstrated resistance to isolates of P. capsici in addition to otber pathogens, but its usefulness as a rootstock is limited (20,27,30,31). Tbe eggplant lines EG195 and EG203 were intermediately to fully resistant to all 14 of tbe P. capsici isolates tested in tbis study.…”
Section: Discussionmentioning
confidence: 97%
“…Root rot is one of the most serious disease symptoms, which can result in plant wilting and death when plants are infected with P. capsici [1]. The spread of P. capsici is accelerated by high temperatures and humidity and is managed through cultural practices, fungicide applications and the use of resistant cultivars [2].…”
Section: Introductionmentioning
confidence: 99%